Metal-Free Graphitic Carbon Nitride Photocatalyst Goes Into Two-Dimensional Time - Zhao, Gang; Yang, Hongcen; Liu, Mengqi; Xu, Xijin (Frontiers in Chemistry, 2018)
Graphitic carbon nitride (g-C3N4) is always a research hotspot as a metal-free visible-light-responsive photocatalyst, in the field of solar energy conversion (hydrogen-production by water splitting). This critical review summarizes the recent progress in the design and syntheses of two-dimensional (2D) g-C3N4 and g-C3N4-based nanocomposites, covering (1) the modifications of organic carbon nitrogen precursors, such as by heat treatment, metal or metal-free atoms doping, and modifications with organic functional groups, (2) the influencing factors for the formation of 2D g-C3N4 process, including the calcination temperature and protective atmosphere, etc. (3) newly 2D g-C3N4 nanosheets prepared from pristine raw materials and bulk g-C3N4, and the combination of 2D g-C3N4 with other 2D semiconductors or metal atoms as a cocatalyst, and (4) the structures and characteristics of each type of 2D g-C3N4 systems, together with their optical absorption band structures and interfacial charge transfers. In addition, the first-principles density functional theory (DFT) calculation of the g-C3N4 system has been summarized, and this review provides an insightful outlook on the development of 2D g-C3N4 photocatalysts. The comprehensive review is concluded with a summary and future perspective. Moreover, some exciting viewpoints on the challenges, and future directions of 2D g-C3N4 photocatalysts are discussed and highlighted in this review. This review can open a new research avenue for the preparation of 2D g-C3N4 photocatalysts with good performances.